Caracterização clínica, epidemiológica e laboratorial das reações hansênicas durante e após poliquimioterapia: análise de potenciais fatores preditivos - Antunes, Douglas Eulálio (2012)
Leprosy, a chronic infectious disease caused by Mycobacterium leprae, still persists as a public health problem in Brazil due to its high potential to cause physical disabilities triggered mainly by leprosy reactions that can occur before, during and or after multidrug therapy. The aim of this study was to characterize the leprosy reactions in its clinical aspect, epidemiological and laboratory in patients diagnosed from 2002 to 2009, a National Reference Center. In this cross-sectional observational study, we used secondary data source, which evaluated 440 cases, with predominance in the reaction of the operational classification MB 80.5% (202/251) of the clinical DT 33.9% (85 / 251), male 68.5% (172/251), Caucasians 53.4% (134/251) and aged 40 to 59 years 52.2% (131/251). Of the total cases, 57% (251/440) had leprosy reactions, 47.9% (211/440) during treatment and 35.9% (158/440) after discharge. The type of reaction was the most prevalent type 1 with 64.5% (136/211) during treatment, and 73.5% (155/211) of reactional episodes occurred in the first three months, averaging 1.6 episodes per patient and 63.9% (101/158) with post treatment reaction, which in 91.1% of leprosy reactions occurred within 15 months the period mentioned, whose average response was 1.9 per patient. Dermal smear (OR: 6.39, p <0.001) and ELISA serology anti-PGL-1 (OR: 4.77, p <0.001) positive at diagnosis, presence of leukocytosis (OR: 9.97, p < 0.001), thrombocytopenia (OR: 5.72, p <0.001) and elevated serum lactate dehydrogenase (OR: 2.38, p = 0.001) were predictive factors for the emergence of both reactions (Type 1 and Type 2) during treatment, and there was a positive correlation between the number of reactions that period with the bacterial index (BI) ≥ 2.3 (r = 0.217, p = 0.0019) and index values ELISA anti-PGL-1 ≥ 2.8 (r = 0.248, p = 0.0007). For the occurrence of post treatment reaction, a positive smear (OR: 8.47, p <0.001) and PCR for detection of DNA of M. leprae (OR: 6.46, p <0.001) in the upper dermal smear, anemia (OR: 2.36, p = 0.013), leukocytosis (OR: 4.14, p = 0.007), thrombocytopenia (OR: 3.70, p = 0.008) were the findings related to potential markers of both leprosy reactions during this period. This epidemiological study identified clinical and laboratory predictors related to the occurrence of leprosy reactions during and after treatment and characterized target groups for interventions to improvements in prevention, monitoring and timely treatment to prevent neurological damage and, consequently, physical disabilities, which has been related stigma to leprosy.